Pengaruh Penerapan Sistem E-Filing Terhadap Kepatuhan Wajib Pajak Aparatur Sipil Negara di Kecamatan Karawang Barat - Hidayyat Hidayyat; Siti Nuridah; Siti Ayu Rosida (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Statistically, the value of taxpayer compliance always increases every year. However, the increase is not in accordance with the target of the Directorate General of Taxes (DGT), this is caused by several things, one of which is filling in the Tax Return (TR) to report tax calculations and/or payments, according to the provisions of tax laws and regulations. In this study, the population is individual taxpayers, namely State Civil Apparatus (SCA) in West Karawang District who are registered at the West Karawang Tax Office and have used the e-filing system using a sample of 100 respondents. The data of this study were obtained from questionnaires (primary) distributed using the incidental sampling method. The results of this study indicate that the implementation of the e-filing system has a positive and significant effect on taxpayer compliance. This is proven through linear regression analysis which obtained an R value of 0.263 and an R square of 0.069, indicating the presentation of the contribution of the influence of the implementation of the e-filing system on taxpayer compliance of 6.9% while 91.1% is influenced by other variables not included in this study. The results of the hypothesis testing carried out using the analysis tool (SPSS 22), namely the t-test, are in accordance with the previously made hypothesis, which shows that the implementation of the e-filing system has a positive and significant effect on taxpayer compliance (State Civil Apparatus in West Karawang District).